Registered cartels in Austria: Coding protocol - Nikolaus Fink; Philipp Schmidt-Dengler; Konrad O. Stahl; Christine Zulehner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
In the period following WW II. until the country accessed the European Union, cartels were legalized in Austria, upon registration with the Austrian Cartel Court. We obtained access to the registration data, and scanned them all towards a microeconomic analysis of contracting behavior between firms competing, in principle, in their respective markets. In this paper, we give a detailed account of our procedure of coding the data from the scanned documents.
Keywords: L410; L430; 330; Collusion; legal cartels; contracts